Is a confidence needed in learning mathematics? - Surya Sari Faradiba; Alifiani Alifiani (Universitas Islam Negeri Maulana Malik Ibrahim, 2019)
Metacognitive blindness is often found in students with unsatisfactory academic performance. However, this study aims to reveal the process of metacognitive blindness that occurs during problem solving experienced by students with quite good academic performance. The data collected is in the form of words obtained through interviews and pictures of the work of research subjects. Description of data analysis and interpretation of the meaning of findings using text analysis. Analysis is carried out in all phases of problem solving, including analyzing, exploring, planning steps to solve problems, implementing a problem solving plan, and checking again. The results of qualitative analysis show that subjects who are students with good academic performance can experience anomalous results during the problem solving process. In this study, the anomalous result in question is a condition where the subject feels anomaly during the problem solving process, where the anomaly is actually not there. In this case, subjects who have good academic performance tend to have too much confidence. This makes the performance in the problem-solving process less optimal.